Multifocal Desmoplastic Infantile Ganglioglioma/Astrocytoma (DIA/DIG): An Institutional Series Report and a Clinical Summary of This Rare Tumor - Wang, Qiguang; Meng, Jinli; Cheng, Jian; Zhang, Si; Hui, Xuhui; Li, Qiang; Liu, Wenke; Ju, Yan; Sun, Lin (Frontiers in Oncology, 2022)
Aim Multifocal desmoplastic infantile ganglioglioma/astrocytoma (DIA/DIG) has rarely been reported. Here, two cases have been presented, reviewing the literature and proposed treatment algorithms for this rare tumor. Patients and Methods We report two patients diagnosed with multifocal DIA/DIGs in West China Hospital. In addition, a literature review was performed, in October 2019, on case reports of DIA/DIGs with multifocal lesions. The clinical and radiological features, treatment, and outcome of this rare disease were discussed. Results DIA/DIGs with multifocal locations were rare, and only thirteen cases (including ours) had been reported. This series included 8 males and 5 females with a mean age of 31.4 ± 45.7 months (range, 3-144 months). The supratentorial hemisphere, suprasellar region, posterior cranial fossa, and spinal cord were frequently involved. Ten patients (76.9%) received surgical resection for the symptomatic lesions and three patients (23.1%) underwent biopsy. Seven patients received chemotherapy postoperatively. Six individuals had tumor recurrences during the follow-up period, while three patients had tumors that spontaneously regressed. Finally, two patients died of tumor progression and one patient died of respiratory insufficiency and hypothalamic dysfunction. Conclusions Multifocal DIA/DIGs have more aggressive clinical behavior and poor outcome despite benign histology. DIA/DIGs should be included in the differential diagnosis of multifocal brain tumors in children. The mainstay of treatment is surgical resection; adjuvant treatment with chemotherapeutic drugs is unknown and requires additional research.